2022
DOI: 10.1038/s41416-022-01724-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumour surveillance protocols and outcomes in von Hippel-Lindau disease in a national health service

Abstract: Background Von Hippel-Lindau (VHL) disease is an inherited tumour predisposition syndrome and a paradigm for the importance of early diagnosis and surveillance. However, there is limited information on the “real world” management of VHL disease. Methods A national audit of VHL disease in the United Kingdom. Results VHL disease was managed mostly via specialist clinics coordinated through regional clinical genetics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Globally, there is little information available on access to appropriate surveillance outside of centres with a research interest in VHL disease. In the UK, there are no centrally commissioned VHL services although majority of care is via speciality clinics coordinated through medical genetics services [43].…”
Section: Mdt Management Of Vhl Disease: An Emerging Role For the Medi...mentioning
confidence: 99%
“…Globally, there is little information available on access to appropriate surveillance outside of centres with a research interest in VHL disease. In the UK, there are no centrally commissioned VHL services although majority of care is via speciality clinics coordinated through medical genetics services [43].…”
Section: Mdt Management Of Vhl Disease: An Emerging Role For the Medi...mentioning
confidence: 99%
“…VHL disease predisposes to the development of renal cysts and ccRCCs, and a single individual can present with multiple lesions [ 82 ]. A nationwide audit reported a median of 2–3 RCCs per individual [ 83 , 84 ]. In renal cysts, foci of dysplasia or RCC can be present, especially in complex cysts [ 82 , 84 ].…”
Section: Von Hippel-lindau Disease and Ccrccmentioning
confidence: 99%
“…A national audit of VHL disease showed that MRI was the most common detection modality, followed by CT and ultrasonography, especially for bigger lesions [ 83 ]. MRI is better at detecting small renal masses than ultrasonography [ 83 ] and, although its sensitivity is inferior to that of abdominal CT, its use is preferred in screening protocols to spare patients from cumulative exposure due to ionizing radiations starting at a young age [ 83 , 99 ].…”
Section: Von Hippel-lindau Disease and Ccrccmentioning
confidence: 99%
See 1 more Smart Citation